The Impact Of Tax Reforms On Stock Market Efficiency: A Study On Policy Changes And Market Dynamics - Yessica Amelia; Ngadi Permana; Sarah Fitriyani (Cahaya Abadi Publisher, 2025)
This study examines the impact of tax reforms on stock market efficiency, focusing on how policy changes influence liquidity, price dynamics, and information flow within financial markets. Using the Tax Cuts and Jobs Act (TCJA) of 2017 as a case study, this research explores how tax reductions affect corporate decision-making, trading behavior, and the efficiency of asset pricing. The findings suggest that while tax reforms can enhance short-term liquidity and improve transparency in stock pricing, they also introduce challenges such as increased market volatility and information asymmetry. These results underscore the importance of aligning tax policies with market stability goals to optimize investor confidence and overall market efficiency.